News in Brief and Their Role in Public Understanding of News Content in Iraqi Satellite TV - Hamza, Ra’ad Jasim; Fadhel, Ali Abass (ALBAHITH ALALAMI, 2014)
News feeds are at the forefront of news forms that are close to the public’s attention for their rapid news content in two directions: its speed in summarizing events in one or two sentences easy to be understood and realized. highlight the most important contents of screenings or news broadcast. The researchers felt that the importance of these brief news compared to news broadcast, breaking news and news subtitle are still ambiguous, as well as their contents. The researchers selected the city of Baghdad as a community to research and prepare a questionnaire form containing (11) questions. The questionnaires were distributed to a non-relative stratified sample consisting of (150) respondents representing the classes or categories of Baghdad society. The researchers identified several objectives, including knowing the most important groups interested in the brief news as well as the most important contents of the favorite and knowing the Iraqi satellite channels seen by the layers of Iraqi society. The most important findings of the researchers could be: The number of viewers of the Iraqi satellite channels in Baghdad (87%) of the respondents, most of them are males and staff category. However, the most important reasons not to watch the brief news are that the ones do not give full details of the news. Al-Iraqiya Channel came first among the channels seen by the public. While (19%) of respondents stressed that the brief news are considered a major source of information about the head news broadcast. Whereas the political and security implications were the most viewed by the public.